(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article analyzes the social and legal foundations of family institution reforms in New Uzbekistan, the process of their formation, key principles, and future directions. The initiatives on the family institute was proposed.